Customers satisfaction towards the credit department services quality at Agrobank, Jalan Hang Tuah Melaka / Lia Badie - Badie, Lia (Faculty of Business and Management, 2009)
This research is about a study on Customers’ satisfaction towards the Credit Department Service Quality at Agro Bank, Jalan Hang Tuah Melaka. This study will examine and measure the level of customer’s satisfaction and the relationship of the items that will influence their satisfaction with the service provided to them in order to increase and gain more satisfaction of Agro Bank Customers. Factors such as service quality and customers satisfaction have been identified in order to investigate whether or not these factors have relationship with customer’s satisfaction. Chapter 1 consists of Introduction and Background of the research, chapter 2 consists of Literature Review, chapter 3 consists of Research Methodology, chapter 4 consists of Finding and Data Analysis and chapter 5 consists of conclusion and Recommendations. The sample size for this study is 58 respondents which are customers of Agro Bank. Data are obtained using two methods that are Primary data and Secondary data. Respondents are required to answer the questionnaire that contains elements that potentially have relationship with Service Quality and Customer’s Satisfaction. Finding showed that most of the customers were satisfied with the services provided by Agro Bank. The researcher is also able to give some recommendation on how to improve and increase customer’s satisfaction.